2018
DOI: 10.1038/s41366-018-0023-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the metabolic effects of diet-induced obesity vary by age of onset

Abstract: Sex differences in the effect of diet-induced obesity (DIO) have been reported in juvenile mice. However, thorough side by side comparisons of the effects of DIO in males and females at different ages of onset have yet to be examined. We hypothesized that aged females would lose their protection, relative to males, from the effects of DIO. We examined the effect of DIO on body weight and glucose tolerance in juvenile, young adult, and middle-aged male and female mice. Our data show DIO in juvenile mice causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
74
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 13 publications
21
74
0
1
Order By: Relevance
“…Energy expenditure and obesity are regulated by hypothalamus, in particular, the ARC that consists of POMC neurons. Studies have shown that POMC neurons modulate sex-specific changes of body weights in diet-induced obesity (Burke et al, 2016;Medrikova et al, 2012;Salinero et al, 2018). Here we show that POMC neuron-specific miR-7 knockdown and miR-17-92 knockout mice display sex-different response to high fat diet.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Energy expenditure and obesity are regulated by hypothalamus, in particular, the ARC that consists of POMC neurons. Studies have shown that POMC neurons modulate sex-specific changes of body weights in diet-induced obesity (Burke et al, 2016;Medrikova et al, 2012;Salinero et al, 2018). Here we show that POMC neuron-specific miR-7 knockdown and miR-17-92 knockout mice display sex-different response to high fat diet.…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, we have found that only female miR-7 knockdown mice and male miR-17-92 knockout mice display diet-induced obesity. Previous reports have shown sex-specific changes of body weights, which is regulated by POMC neurons (Burke et al, 2016;Medrikova et al, 2012;Salinero et al, 2018). However, how POMC neurons modulate sex-specific changes of body weight is unclear.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, mouse and other in vivo preclinical models differ from humans in many known and unknown details, both intrinsic (eg, genetic, immune, 159-164 surface area: volume ratio, lifespan 165 ) and extrinsic (eg, captivity, diet, history), which, depending on the research question, may substantially affect translational relevance. [169][170][171][172] A wide variety of approaches are used to increase the predictive validity of mouse models. [169][170][171][172] A wide variety of approaches are used to increase the predictive validity of mouse models.…”
Section: Selection Of a Mouse Modelmentioning
confidence: 99%
“…Further, while 321 pre-menopausal women have considerable protection from numerous metabolic disease states 322 [39], the prevalence of overweight/obesity is higher in women in all age groups [40]. Chronic ad 323 libtum high-fat diet rodent studies of varying lengths have demonstrated that males and females 324 gain similar amounts of body weight, with females having greater body fat percentages [41,42]. 325…”
Section: Activity Components Of Energy Metabolism 252mentioning
confidence: 99%
“…can not determine the magnitude of activation of the different non-shivering thermogenic 409 tissues, which could potentially differ by baseline EE or sex. Third, the assessment of diet-410 induced weight gain in 9 -11 week old mice could be confounded by the previously observed 411 dependence of weight gain on age of diet initiation and sex [41]. Fourth, previous mouse work 412 has demonstrated that male mice defend different body core temperatures at different ambient 413 temperatures [27,65].…”
Section: Limitations 400mentioning
confidence: 99%